PENANAMAN KESADARAN PENTINGNYA PENDIDIKAN DAN MOTIVASI BELAJAR SEBAGAI UPAYA PENCEGAHAN PUTUS SEKOLAH BAGI SISWA SDN LEMAH ABANG - Isnaini Mahuda; Dewi Anita Layli; Regita Alfianti; M. Adlan Abizar; Nur Aini F (Jubaedah : Jurnal Pengabdian dan Edukasi Sekolah (Indonesian Journal of Community Services and School Education), 2022)
Education is the key in determining the future of the nation's next generation. Seeing the importance of education, the government always tries to give serious attention in overcoming problems in the field of education. One of the problems that currently plagues the world of education is the high dropout rate for children. Banten Province is a province in Indonesia where cases of dropping out of school in children are still quite high, including Serang City as the provincial capital. Team of KKM-PkM UNIBA 04 with a service location in Warung Jaud Village, Kasemen District, Serang City seeks to help provide solutions in preventing children from dropping out of school through motivational seminars with the aim of instilling awareness of the importance of education and motivating children to be enthusiastic about learning. The activity was carried out at SDN Lemah Abang with students in grades 5 and 6. The method used consisted of several stages including the pre-activity stage, the activity preparation stage, the activity implementation stage and the activity evaluation stage. As for the results of this activity, it was concluded that: 1) community service activities in the form of motivational seminars went well and were followed with great enthusiasm by the seminar participants; 2) this activity can be a preventive effort in dealing with cases of children dropping out of school by instilling awareness of the importance of education and motivating students to be enthusiastic about learning